Abrahamic Religiosity Scale: development and initial validation - Khodayarifard, Mohammad (Mental health, religion & culture, 2018)
There are a large number of commonly used measures of religiosity, yet these measures have been developed within a specific culture or religion. Based on the commonality of Abrahamic religions (i.e., Judaism, Christianity and Islam), the present study aimed to develop an initial cross-cultural validation of the Abrahamic Religiosity Scale (ARS). The data were collected from 12 countries from Asia, Europe, Africa and America, and exploratory factor analysis resulted in a 35-item, one-dimensional scale. Confirmatory factor analysis yielded a 28-item with one factor. The scale showed sufficient internal consistency with an adequate alpha coefficient (α = .95). Moreover, the correlation coefficients between items and the total score of ARS ranged between .36 and .70. Therefore, the ARS may be used as a psychometrically robust measure in cross-cultural studies on religiosity. Validation of the ARS is strongly recommended within specific cultures and languages.